Fibre-Optic Temperature Sensor Using Bragg Structure - Kukhtin, S. М.; Hnatenko, O. S. (My University, 2023)
Fiber-optic sensing has established itself as an innovative and versatile measurement technology for various physical parameters, such as temperature. Moreover, particular properties of optical fibers, in some cases, make fiber-optic sensing only suitable choice due to operation conditions, precision and accuracy, possibility of remote operation. In this paper we present the simple fiber optic temperature sensor system that utilizes reflective Bragg element as a sensing head. The main advantage of the proposed approach relies on the use of widely available low-cost telecommunication devices, such as a DFB laser as a light source and commonly used fiber optics components. Another advantage of the sensor is measurement technique that doesn’t require optical spectrometer or other precise optical measurements such as interferometry. It is shown that by implementing various Bragg structures for the sensing element it is possible to alter optical response thus achieving required characteristics of the sensor. Calculations for Bragg structures are presented for both narrow range sensor suitable for medical use and wide range temperature sensor with ΔT  200 °C. In addition, this paper provides brief review of commonly used fiberoptic temperature sensing techniques, their advantages and application.
Keywords: Temperature sensor; Optical fiber; Fiber Bragg grating; Reflection index